Safety at site (Case study at Library Kerteh & Masjid Kemasik) / Mohd Izzat Fahmi Ismail - Ismail, Mohd Izzat Fahmi (2015)
Practical training or also known as industrial training outside the institution is a condition that all student need to get through. Some other course, their industrial training is on semester 4 or semester 5. After that they need to continue their study as usual. But for course Building Surveying, the industrial training is for the last semester. The procedure of applying the place of training is before the second last semester had end. So the student needs to confirm their place of industrial training as soon as possible to avoid any unwanted things happen. The company for industrial training must be related with the course. So the student can learn more and get more experience about the course. Also learn and look how the surveyors work. During the training, the student must write a simple written report in log book that was given by the lecturer. What are the student do every day must be write in the log book by write and also picture for the evidence. The students also need to do the report during the training. The title of the report must be the project that the company is currently doing. The report must be submitted at the end of the industrial training.